Pengembangan Video Animasi Toonly Pada Mata Kuliah Bunpo Shochukyu (Bab 38-40) - Putu Ratih Megantari; Yeni Yeni; Kadek Eva Krishna Adnyani (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This research aims to develop three learning animated videos with a duration of 4-6 minutes in mp4. Format. This research is a Research and Development using MDLC (Multimedia Development Life Cycle) method that are introduced by Luther-Sutopo (in Binanto, 2010). The purpose of this research is to help the teacher and student on the lesson session, also to help motivate the student interest in learning Bunpo Shochukyu. Collecting reference data was done by interviewing the teacher and giving questionnaire to the students. The data that are obtained was analyzed using qualitative and quantitative method. The tests are Alpha Test which are tested with Media Expert and Material Expert, whereas Beta Test is tested with small group of second semester Japanese Language Education Students. Result of the first test is 56 points (Very Good) and second test is 57 points (Very Good) from the Media Expert and 48 points at first test (Good) and second test is 49 points (Good) from Material Expert of Alpha Test, whereas the average results of Beta Test are 101 points (Good). With these tests results, the animated learning videos can be utilized in the subject of Bunpo Shochukyu Chapter 38-40